Cloning a novel reduced-height (Rht) gene TaOSCA1.4 from a QTL in wheat - Lv, Guangde; Jin, Xuemei; Wang, Hui; Wang, Yijun; Wu, Qun; Wu, Haimeng; Jiang, Fangshan; Ma, Yanming; An, Yanrong; Zhang, Mingxia; Guo, Ying; Li, Sishen (Frontiers in Plant Science, 2024)
Reducing plant height (PH) is one of the core contents of the “Green Revolution”, which began in the 1960s in wheat. A number of 27 reduced-height (Rht) genes have been identified and a great number of quantitative trait loci (QTLs) for PH have been mapped on all 21 chromosomes. Nonetheless, only several genes regulated PH have been cloned. In this study, we found the interval of QTL QPh-1B included an EST-SSR marker swes1079. According to the sequence of swes1079, we cloned the TaOSCA1.4 gene. We developed a CAPS marker to analyze the variation across a natural population. The result showed that the PH was significantly different between the two haplotypes of TaOSCA1.4–1B under most of the 12 environments and the average values of irrigation and rainfed conditions. This result further demonstrated that TaOSCA1.4 was associated with PH. Then, we validated the TaOSCA1.4 via RNAi technology. The average PHs of the wild-type (WT), RNAi lines 1 (Ri-1) and 2 (Ri-2) were 94.6, 83.6 and 79.2 cm, respectively, with significant differences between the WT and Ri-1 and Ri-2. This result indicated that the TaOSCA1.4 gene controls PH. TaOSCA1.4 is a constitutively expressed gene and its protein localizes to the cell membrane. TaOSCA1.4 gene is a member of the OSCA gene family, which regulates intracellular Ca2+ concentration. We hypothesized that knock down mutants of TaOSCA1.4 gene reduced regulatory ability of Ca2+, thus reducing the PH. Furthermore, the cell lengths of the knock down mutants are not significantly different than that of WT. We speculate that TaOSCA1.4 gene is not directly associated with gibberellin (GA), which should be a novel mechanism for a wheat Rht gene.